KEPRIBADIAN TOKOH DALAM NOVEL PARADIGMA KARYA SYAHID MUHAMMAD - Lestari, Depi Yanti; Sulissusiawan, Ahadi; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to find out the results of the analysis of the character's personality, psychological problems and factors that influence the character's personality in the novel Paradigma by Syahid Muhammad. This research is in the form of qualitative descriptive method. This study uses a literary psychology approach. The data source for this research is the novel Paradigma by Syahid Muhammad with the data in the form of excerpts from the novel's sentences which lead to the object of analysis. Data collection techniques using documentary study techniques. The results of this study are the character's personality which consists of aspects of id, ego, superego. selfishness, feeling guilty, indifference, pleasure, stubbornness, resisting pain, reluctant to get angry, refusing to be approached, aware of what is happening, uncomfortable, uncontrollable, unyielding, holding back anger and hatred. The psychiatric problems found are adjustment disorders, anxiety disorders, mood disorders and suicide, and personality disorders. There are personal factors that influence the appearance of the character's personality aspects which include biological factors, curiosity motives, love motives, self-esteem motives, the need to seek identity, motives of values, attitudes, and emotions.